2011
DOI: 10.5139/jksas.2011.39.6.498
|View full text |Cite
|
Sign up to set email alerts
|

Trim Range and Characteristics of Autorotation(II): Advance Ratio Variation and Flapping Characteristics

Abstract: The flapping characteristics and advance ratios at torque equilibrium state of autorotation were investigated when the airspeed, shaft angle, and pitch angle were varied. To simulate the airspeed increase, the aerodynamic data analyzed by using the compressible Navier-Stokes solver and Pitt/Peters inflow theory were used. Transient Simulation Method(TSM) was used to catch the torque equilibrium states. The maximum flapping angles at torque equilibrium state were correlated to the airspeed, shaft angle, and pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The simulation results showed that the collective pitch range shrinks with a reducing rotor shaft angle. Then, in consecutive research (17) , the TSM was used to analyse a full-scale rotor. In that study, to explore the pitch setting range when a rotor experiences an increasing forward airspeed, a compressible Navier-Stokes solver was used to support the airfoil look-up table.…”
Section: Introduction 11 Background and Motivationmentioning
confidence: 99%
“…The simulation results showed that the collective pitch range shrinks with a reducing rotor shaft angle. Then, in consecutive research (17) , the TSM was used to analyse a full-scale rotor. In that study, to explore the pitch setting range when a rotor experiences an increasing forward airspeed, a compressible Navier-Stokes solver was used to support the airfoil look-up table.…”
Section: Introduction 11 Background and Motivationmentioning
confidence: 99%